ALIH AKSARA DAN ALIH BAHASA TEKS BUNGA RAMPAI ACEH - Oktaviani, Ayu; Juita, Novia; Zulfadhli, Zulfadhli (Universitas Negeri Padang, 2017)
This article was written to: (a) present the description of the manuscript about translation and change language of story about Bunga Rampai Aceh text, and (b) present change language of story about Bunga Rampai Aceh.This research is a philology research. The object of this article were translation and change language of story about Bunga Rampai Aceh text. This manuscript was collection of Aceh Museum. The method used in this article tailored to the stage of research. At the stage of data collection used method literature study and field study method. At the stage of description of the manuscript used descriptive method. At the stage of transliteration used trasliteration method. At the stage of change language used change language method.The result of this research was in the form of presentation of text that can be read and can be understood by the today’s public about translation and change language of story about Bunga Rampai Aceh text. The result of this research also present the text that has been adapted to Ejaan bahasa Indonesia (EBI). This manuscript tells about a prayer to issue a star, the language of the body, and tells about how to sakaratul maut began. In the manuscript about Bunga Rampai Aceh text there was a vocabulary that shows many variety of old Malay language in it. This is for the purity of the script language was maintained.Keywords: translation, change language, text, philology